Clinical, endoscopic, and histologic features of eosinophilic inflammation of the gastrointestinal tract in pediatric liver transplant patients. (12th September 2013) - Parashette, Kalyan Ray; Zeytinoglu, Meltem; Kernek, Kevin; Molleston, Jean P.; Subbarao, Girish
Abstract: Immunosuppression during the post‐transplantation period has led to dramatic outcome improvements in PLTR patients. There have been reports describing the development of food allergies and an increased predilection for development of EGI in PLTR. We aimed to identify the clinical, endoscopic and histologic features of EGI in PLTR patients. In this retrospective case series we analyzed medical record of all PLTR who underwent EGD and/or colonoscopy at our institution from 2000 to 2006. From 2000 to 2006, 32 PLTR patients underwent endoscopic evaluation. Seventeen (53%) of 32 patients were diagnosed with EGI. Endoscopic abnormalities were seen in the esophagus, stomach, and small intestine in 11 (65%), 11 (65%), and four (24%) patients, respectively. Eosinophilic inflammation was seen in the esophagus, stomach, and small intestine in 13 (76%), 10 (59%), and five (29%) patients, respectively. Nine of 17 patients underwent colonoscopy and endoscopic abnormalities were seen in four (44%) patients. Five patients (56%) had eosinophilic inflammation. In conclusion, we have characterized the clinical, endoscopic, and histologic features of EGI. Histologic and endoscopic examination reveals that, when present, EGI is often found at multiple segments along the gastrointestinal tract.